Financial Performance Analysis Of PT. Suparma Tbk Year 2023-2024 Using Effiency Ratio - Hargo Dedali, Shindu (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2025)
This research was created with the aim of allowing users to see the Financial Performance of PT. Suparma Tbk in 2023-2024. So if the user wants to invest funds in PT. Suparma Tbk can see how big the financial performance of PT. Suparma Tbk, especially looking at the efficiency of PT. Suparma Tbk in Inventory turnover and Receivables turnover whether it is going well or not going well. And researchers want to examine financial performance using efficiency ratios, which include the Inventory Turnover Ratio & Receivables Turnover Ratio. Because if the Company can optimize Company Efficiency, it will be able to increase profits for the Company. If the company is profitable, employee welfare will be guaranteed and the facilities received by employees will be even better Keywords: Financial Performance; Inventory Turnover Rasio; Receivables Turnover Rasio